Analisis Karakteristik Pasien Diabetes Melitus Tipe 2 di Puskesmas Dukuh Kupang Surabaya - Wirayudha, Sri Annung; Inawati Inawati; Agusaputra, Harman; Hernanda, Pratika Yuhyi (Lembaga Pengembangan Kinerja Dosen, 2025)
Type 2 Diabetes Mellitus is a chronic metabolic disease with a continuously increasing global prevalence. Understanding the characteristics of patients is essential for early detection, clinical management, and prevention of complications. Objective: To identify the characteristics of patients with type 2 diabetes mellitus at Dukuh Kupang Primary Health Center, Surabaya, based on age, gender, routine check-ups, duration of illness, body mass index (BMI), and complications. Methods: This descriptive observational study employed a cross-sectional approach and was conducted from January to February 2025. A total of 30 respondents were selected using purposive sampling. Data were obtained from medical records and supplemented by questionnaires. Results: Most patients were aged >60 years (57%), female (60%), had a normal BMI (50%), and adhered to routine medical check-ups (97%). The majority had been diagnosed for more than 5 years (53%) and experienced complications (83%), with neuropathy being the most common type (73%). Conclusion: Patients with DM type 2 at Dukuh Kupang Health Center were predominantly elderly, female, had a normal BMI, and experienced neuropathic complications.